Implementation of Police Duties to Support the Implementation of Health Protocols During the Covid-19 Pandemic in Order The Realization of a Conducive Kamtibmas Atmosphere (baubau city case study) - Deddy Mursanto (Jurnal Hukum Volkgeist, 2021)
Police responsibility is very complex ranging from in public service to supporting security against the security of the State. Seeing or studying the task of the Police to the scale of the Police then the author wants to describe the duties and responsibilities of the National Police mandated by law in carrying out its duties and responsibilities by taking samples, namely baubau city police in controlling the mandate of the Law and information related to the handling of the Covid-19 Pandemic where the city of Baubau was not spared the impact of the pandemic. The purpose of this study is to understand the role of the police in the implementation of kamtibmas during the Covid 19 pandemic in Baubau City. The types of data used in the study are primary and secondary data collected from the interview process and literature studies, which will then be analyzed qualitatively with the steps that have reduced the data. The results of this study concluded the role of Bhabinkamtibmas and Intelkam is very basic and supports all police duties in maintaining public order and looking for basic information about people who do not comply with the recommendations of health protocols in the community during the Current Covid-19 Pandemic and provide input to the community to prevent the emergence of new perpetrators of crimes due to the Covid-19 pandemic by giving input on what should be done by the community.